2022
DOI: 10.1007/s00024-022-03186-7
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of Aquifer Boundary by Two Vertical Superconducting Gravimeters in a Karst Hydrosystem, France

Abstract: Mass distribution on Earth is continuously changing due to various physical processes beneath the Earth's surface or on the surface. Some of the primary sources for these mass displacements are tidal forces, atmospheric and oceanic loading, and seasonal changes in continental water distribution. The development of relative cryogenic gravimeters, the Superconducting Gravimeters (SGs), has made it possible to characterize and monitor such mass variations at orders of magnitudes as small as a few nm/s 2 (1 nm/s² … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…The available long time series revealed that there is an aging effect on the SG gravimeters, that starts with an age of 10-15 years of the instrumentation, which possibly requires exchange of some electronics (Jahr & Stolz, 2022). The low noise underground laboratory in Rustrel (France) is equipped by a vertical disposition of two superconducting gravimeters (Kumar et al, 2022) providing a large sensitivity of this gradiometric arrangement to the water storage changes. It was shown that for this laboratory located in a karstic geological medium, the greatest mass contribution comes from the hydrologic storage changes in the unsaturated zone, and the gradiometric disposition is sensitive to lateral mass changes up to a distance of 2500 m. The work of Elsaka et al (2022) deals with a calibration process of a new SG through a parallel record and comparison of earth tides signal in the Walferdange Underground Laboratory for Geodynamics in the Grand Duchy of Luxembourg.…”
Section: Introductionmentioning
confidence: 99%
“…The available long time series revealed that there is an aging effect on the SG gravimeters, that starts with an age of 10-15 years of the instrumentation, which possibly requires exchange of some electronics (Jahr & Stolz, 2022). The low noise underground laboratory in Rustrel (France) is equipped by a vertical disposition of two superconducting gravimeters (Kumar et al, 2022) providing a large sensitivity of this gradiometric arrangement to the water storage changes. It was shown that for this laboratory located in a karstic geological medium, the greatest mass contribution comes from the hydrologic storage changes in the unsaturated zone, and the gradiometric disposition is sensitive to lateral mass changes up to a distance of 2500 m. The work of Elsaka et al (2022) deals with a calibration process of a new SG through a parallel record and comparison of earth tides signal in the Walferdange Underground Laboratory for Geodynamics in the Grand Duchy of Luxembourg.…”
Section: Introductionmentioning
confidence: 99%